Dianetics the modern science of mental health - Hubbard, L. Ron (La Fayette Ron) 1911-1986 (Bridge Publications, Inc., 2007)
If you've ever felt there was something holding you back in life, ruining your plans and stopping you from being who you want to be, you were right. The fact is, there is a single source of all your problems, stress, unhappiness and self-doubt. It's called the reactive mind - the hidden part of your mind that stores all painful experiences and then uses them against you. Dianetics gets rid of the reactive mind. It's the only thing that does. With over 20,000,000 copies in dozens of languages, Dianetics has remained a bestseller for more than fifty years. Now used in more than 150 nations, Dianetics brings dramatic and permanent improvement to people all over the world. Read Dianetics and discover: * The real reason for unexplained pains, negative emotions and unhappy relationships in your life. * Exactly what is destroying your belief in yourself and how Dianetics helps you get rid of it so you become more you; * The precise technology that blows away the barriers in your life - forever. Don't live with insecurity, negative thoughts and irrational behavior. Use Dianetics and get rid of your reactive mind. Have you ever wondered how your mind works? Your mind records pictures of everything you experience throughout life. These "mental image pictures" ARE your memory. Through mental image pictures you can see the past, hear what was said, feel, taste and smell things from long ago or just from yesterday. Your perception of mental image pictures - however vague at first - can be sharpened with Dianetics. Mental image pictures are used continually to solve problems, imagine and remember things. L. Ron Hubbard's #1 New York Times bestseller, Dianetics: The Modern Science of Mental Health, will tell you much more about mental image pictures, how the mind works and even the purpose of the mind.